Psychological factors influencing customers’ acceptance of smartphone diet apps when ordering food at restaurants - Okumus, Bendegul; Ali, Faizan; Bilgihan, Anil; Ozturk, Ahmet Bulent (International journal of hospitality management, 2018)
•Examines the adoption of smartphone diet applications by restaurant customers.•Uses the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical base.•Study results suggest several factors that influence customers intentions to use smartphone diet applications. This paper examines the adoption of smartphone diet apps by restaurant customers and, more specifically, the psychological factors that influence their intention to use such apps when ordering food at restaurants. Data was collected from 395 individuals and analyzed using partial least squares structural equation modeling. Results showed that customers’ intention to use smartphone diet apps is predicted by expected performance of the application, anticipated effort of usage, social influence, and degree of user innovativeness. Following the Unified Theory of Acceptance and Use of Technology (UTAUT), this study proposes five determinants of mobile diet apps’ usage intentions: performance expectancy, effort expectancy, social influence, facilitating conditions, and personal innovativeness. Based on the study results, theoretical and practical implications are provided for scholars, health professionals, restaurant operators, and smartphone application developers.